IMPLEMENTASI E-FILLING DAN KUALITAS PELAYANAN PADA KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KANTOR PELAYANAN PAJAK (KPP) BANDAR LAMPUNG - Eha Nugraha; Aderina Kusuma Harahap; Hesti Widi Astuti (Jurnal Akuntansi Indonesia, 2018)
Abstract : The results of this study are as follows, the analysis of the effect of X1 on X2 from the above analysis, the significance value of X1 is 0.000 <0.05, so it can be concluded that the e-filling implementation variable (X1) has an effect on service quality (X2). to Y2 from the above analysis, it was obtained a significance value of X1 of 0.000 <0.05, the analysis of the effect of X2 on Y2 from the above analysis obtained a significance value of 0.122> 0.05, the analysis of the effect of X1 on Y2 from the above analysis obtained a significance value of 0.035 < 0.05 so it can be concluded that the e-filling implementation variable (X1) has an effect on individual taxpayer compliance (Y2). e-filling (X1) affects the compliance of individual taxpayers (Y2). Keywords : e-filling, service, taxation, compliance